Investigation on the Sensitivity Distribution in Electrical Capacitance Tomography System - Pan Jiang; Shidong Fan; Ting Xiong; Haofei Huang (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The gas-solid-liquid three-phase flow is a very complicated flow pattern in pipeline transportation. By using electrical capacitance tomography (ETC) it can acquire the permittivity distribution of the multi-phase. The sensitivity distribution in ETC may affect the analysis of the permittivity distribution of the multi-phase. However, very limited work has been done in this issue. In order to investigate the sensitivity distribution in ETC, this paper employs the finite element method (FEM) to establish the principle and components of ECT. The FEM model of the sensitivity distribution as a function of the inter-electrode capacitance was discussed. Simulation tests were carried out to calculate the charge on the electrode pairs to access the potential distribution of the ETC. The analysis results show that the dielectric have great influence on the capacitance value and small distance between the electrode pair and the sensitivity field will produce high sensitivity value. Hence, the findings of this work can provide reference for the design of ECT in practice. DOI: http://dx.doi.org/10.11591/telkomnika.v11i12.3611